2014
DOI: 10.4322/rbcv.2014.387
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do leite bovino nas diferentes estações do ano no estado do Rio Grande do Norte

Abstract: ResumoObjetivou-se com este trabalho avaliar indicadores da qualidade do leite cru de tanques de expansão em dois períodos do ano (seco e chuvoso) na região agreste do estado do Rio Grande do Norte. Para isso, foram coletadas amostras de leite cru diretamente do tanque de expansão de oito propriedades no período de janeiro de 2010 a março de 2012. Os índices mensais médios de precipitação foram coletados do banco de dados da Empresa de Pesquisa Agropecuária do Rio Grande do Norte. As amostras foram analisadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 2 publications
1
2
0
10
Order By: Relevance
“…The ESD values of the present study were higher than the results obtained by Gonzalez et al (2004), which were 8.39 (rainy season) and 8.42% (dry season) and by Martins et al (2006) raw milk samples stored for 72 h at the production source in the different seasons are in line with Brasil (2011), who found minimum fat, protein, EST and ESD contents of 3.0; 2.9, 11.4 and 8.4%, respectively. Similar results were found by Andrade et al (2014) where medios fat values (3.48%); protein (3.29%); EST (12.13%) and ESD (8.65%) were seen in the dry hazard. Already in the rainy hazard were found the following results for fat (3.59%); protein (3.31%); EST (12.25%) and ESD (8.66%).…”
Section: Resultssupporting
confidence: 76%
“…The ESD values of the present study were higher than the results obtained by Gonzalez et al (2004), which were 8.39 (rainy season) and 8.42% (dry season) and by Martins et al (2006) raw milk samples stored for 72 h at the production source in the different seasons are in line with Brasil (2011), who found minimum fat, protein, EST and ESD contents of 3.0; 2.9, 11.4 and 8.4%, respectively. Similar results were found by Andrade et al (2014) where medios fat values (3.48%); protein (3.29%); EST (12.13%) and ESD (8.65%) were seen in the dry hazard. Already in the rainy hazard were found the following results for fat (3.59%); protein (3.31%); EST (12.25%) and ESD (8.66%).…”
Section: Resultssupporting
confidence: 76%
“…Mesmo com o consumidor, cada vez mais consciente e informado quanto aos produtos oferecidos nos mercados, estudos ainda apresentam condições microbiológicas insatisfatórias para os derivados do leite (Andrade et al, 2014;Cunha Neto et al, 2005;Leite Júnior, 2013;Reis et al,2014). Os derivados do leite são alimentos altamente susceptíveis à contaminação por fornecerem um ótimo meio de cultivo bacteriano e por terem uma carga proteica e lipídica alta.…”
Section: Resultsunclassified
“…These results corroborate the data of Gonzalez et al (2004), who showed that excessive rainfall promotes higher mastitis rates. By contrast, Andrade et al (2014) reported no effect of season on SCCs in an evaluation of milk from commercial cattle herds within the rugged region of Rio Grande do Norte State, Brazil.…”
Section: Milk Production and Qualitymentioning
confidence: 98%